Design of an Autoreduced Copper in Carbon Nanotube Catalyst to Realize the Precisely Selective Hydrogenation of Dimethyl Oxalate. Issue 6 (9th February 2017) - Ai, Peipei; Tan, Minghui; Ishikuro, Yuki; Hosoi, Yuta; Yang, Guohui; Yoneyama, Yoshiharu; Tsubaki, Noritatsu
Abstract: An autoreduced catalyst that comprised Cu nanoparticles encapsulated inside the nanochannels of carbon nanotubes (Cu@CNTs) was designed and prepared. As a result of the interaction of Cu species with the electron‐deficient interior surface of the CNTs, calcination could realize the autoreduction of copper oxide directly with CNTs as the reductant. In the hydrogenation of dimethyl oxalate (DMO), the autoreduced Cu@CNTs catalyst, which did not need to be prereduced, exhibited an excellent catalytic activity, high target product selectivity, and high catalytic efficiency. Furthermore, the effect of the calcination temperature on the autoreduction degree of Cu@CNTs and the product selectivity in DMO hydrogenation were investigated in detail. The results showed that the autoreduction degree could be tuned easily by changing the calcination temperature, and the highest selectivity of ethanol could be obtained over the catalyst calcined at 500 °C. The findings obtained will inspire the development of other autoreduced catalysts, the reduction degree and catalytic performance of which can be tuned as desired. Abstract : Auto‐awesome ! An autoreduced catalyst that comprises Cu nanoparticles encapsulated inside the nanochannels of carbon nanotubes (Cu@CNTs) that did not need further reduction is prepared and exhibited an excellent catalytic performance for the hydrogenation of dimethyl oxalate (DMO).